Multi-objective Stochastic Volt/VAR Optimization in AC-DC Hybrid Distribution Network Considering Soft Open Point - Pamshetti V.B.; Murty V.V.S.N.; Singh S.P.; Sharma A.K. (My University, 2025)
To cope with different types of distributed energy sources (DERs) and AC/DC loads, combined AC and DC distribution network has emerged as a potential solution for the forthcoming distribution network. However, upward integration of DERs imposes several problems such as voltage violations and system power losses. In order to minimize the system power loss and voltage deviations at the same time, a two-stage multi-objective stochastic Volt/VAR optimization for HDN considering soft open points (SOP) is proposed in this paper. In state 1, a coordination optimization model considering legacy Volt/VAR control devices, status of network switches, DERs, voltage source converter (VSC) and SOP has been established; in stage 2, model predictive control (MPC) based rolling optimization control model has been built, to eliminate the forecasted deviations caused by renewable energy sources and loads. Besides, the original non-convex mixed-integer nonlinear programming (MINLP) problem has been transformed into a mixed-integer second-order cone programming (MISOCP) problem for a feasible solution. The proposed scheme has been verified and authenticated on IEEE 33 bus AC-DC DN. The simulation results reveal the reputation of the proposed methodology on the aforementioned problems. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.